Distribution in Islamic Economic Perspective (Critics to Capitalist) - Telsy Fratama Dewi Samad (Tasharruf: Journal Economics and Business of Islam, 2019)
Distribution is one of the economic topics that is necessary to be discussed, mainly the distribution of wealth because it concerns the effort to achieve prosperity for all levels of society in a country through equitable distribution of wealth. In this article, we will discuss the concept of wealth distribution both from conventional perspective, which is based on capitalist ideology and from the perspective of Islamic economics. As the public understanding about capitalism, it is one of the economic comprehension carried by the Father of Economics "Adam Smith" which emphasizes the individual freedom in managing assets without government intervention. Capitalism has led to injustice and income inequality in the community, causing conflict and creating permanent poverty for the citizens of society. Islam refers the process of distribution of wealth following Islamic principles. Islam prevents the accumulation of wealth in certain small groups and promotes the distribution of wealth to all levels of society. This research is descriptive qualitative based on the study of literature such as books and other literature that are relevant to the problems considered by the author. The purpose of this study is to understand the concept of wealth distribution based on Islamic economic and capitalist economic perspectives. The result of this article concluded that the capitalist wealth distribution system should be replaced by the Islamic economic system that emphasizes the value of freedom as well as the behaviour of human based on religious teachings and the value of justice in ownership.